Pelatihan Vokasional Bagi Penyandang Disabilitas Mental: Evaluasi Reaksi dan Pembelajaran - Caecilia Tridjata; Fariz Al Hazmi; Vera Bella Espransa (Riau Journal of Empowerment, 2024)
People with mental disorders have difficulty finding work, even though they have gone through rehabilitation. Providing vocational training is an effort to help them gain skills to be independent. The evaluation process is very important to carry out in order to see the challenges and successes of the training. The aim of this research is to evaluate vocational training, especially stamp batik skills, through reactions and learning with participants with mental disorders. The research method uses qualitative with a case study approach in batik training with stamping techniques for people with mental disorders at the Jiwa Layang Foundation in the category of residual schizophrenia. The results of the training showed that in the evaluation of the participants' reactions in following the entire training were in the very good category, even though the participants were less focused in paying attention. Meanwhile, at the learning evaluation stage, participants got results in the good category. However, participants were less skilled in making stamping tools. The use of the learning by doing method is a success factor, such as the teaching method used, the work process is carried out in groups and mentoring by instructors. Instructors and assistants must be able to maintain participants' enthusiasm which tends to decrease due to fatigue due to long periods of time. Participants still have to work in groups because making batik requires working in groups